Epidemiologic profile of inflammatory bowel disease in Eastern Mediterranean Region (EMRO) countries: a systematic review and meta-analysis - Zahra Momayez Sanat; Homayoon Vahedi; Reza Malekzadeh; Zeinab Fanni (BMC, 2024)
Abstract Background Inflammatory bowel disease (IBD) consists of two main types: Crohn's disease (CD) and ulcerative colitis (UC). The epidemiology of IBD patients has not been comprehensively studied in EMRO countries; therefore, we conducted this meta-analysis to study the epidemiology of this disease in these countries. Methods We searched four international databases, namely Scopus, Web of Knowledge (ISI), Medline/PubMed, and ProQuest, from inception up to the end of May 2023. The Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) guideline was used to carry out this systematic review and meta-analysis investigation. Using the Joanna Briggs Institute (JBI) Critical Appraisal Checklist, the quality of the selected papers was assessed. Results Based on the results of this study, the incidence of UC in EMRO countries was 2.65 per 100,000 (95% CI: 1.39-3.90), and the incidence of CD was 1.16 per 100,000 (95% CI: 0.73-1.59). The most commonly involved intestinal segment in CD was the terminal ileum (44.7%, 95% CI: 34.7-55.2), followed by the ileum (29.8%, 95% CI: 22.2-38.6), and colon (18.7%, 95% CI: 10.8-30.4). However, in UC patients, extensive colitis was the most common finding (32.3%, 95% CI: 26.4-38.8), followed by proctosigmoiditis (27.9%, 95% CI: 21.1-35.8), left-sided colitis (27.4%, 95% CI: 22.7-32.7), and proctitis (22.6%, 95% CI: 17.5-28.5). Conclusion As a result, we were able to establish the traits of IBD patients in EMRO nations. UC patients had a higher incidence than CD patients. The most common regions of involvement in CD and UC patients, respectively, were the colon and pancolitis. Compared to UC patients, CD patients had a higher history of appendectomy.